“Versions of the South” and “Losing the Human Form”: Latin Americans Look at Themselves in the Mirror of their Art - Jiménez Moreno, Carlos (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
This article focuses on “Versiones del Sur” (2000) and “Perder la forma humana” (2012). These two exhibitions of Latin American art are distinguished within their made-in-Spain genre, because they were the first whose curators were Latin American. Their concepts and contents are analysed, and - in order to present differences between the Anglo-American and Ibero-American perspectives of this art - they are contrasted with those of two exhibitions that also offered ambitious panoramas of the art of the continent: “Arte Iberoamericano: 1820-1980” (1989) and “Artistas latinoamericanos del siglo XX” (1992).